Espacios para la rehabilitación y atención integral de la población adulto joven privada de libertad - Montero-Calvo, Ana María (Instituto Tecnológico de Costa Rica., 2019)
‘’ Arquitecture is an excellent social Act, a utilitarian Art. For her, structure is not the most important aspect, instead, it is the people who live in it. Her main mission is HUMANITY”. _ __Carlos Villanueva. This project provides a contribution to the problem present in the national prison system, specifically the Ofelia Vincenzi Center, the center dedicated to the detention of the young adult population deprived of liberty. This project seeks an architectural proposal that contributes positively to the needs of this population specifically. It takes in consideration the environmental psychology of the structures and spaces, in response to the new demands that have been developed around the building prison strategies, attributing an interrelation of the physical environment with the behavior and the experience of this population. Currently, the Ministry of Justice and Peace of Costa Rica and other entities in defense of Human Rights, show interest in improving socio-spatial aspects in all prisons in the country. This in order to strengthen the rehabilitation process, which is, the main function of privative punishment. Environmental conditions must provide positive opportunities, accompanied by appropriate prison management programs and models. Physical barriers should not prevent but encourage broad communication possibilities. The concept of the building must reflect the high expectations that society places in the social reintegration of those deprived of liberty.
Centro Ofelia Vincenzi
Proyecto de graduación (Licenciatura en Arquitectura y Urbanismo) Instituto Tecnológico de Costa Rica, Escuela de Arquitectura y Urbanismo, 2019.
Keywords: Cárceles; Centros de rehabilitación; Arquitectura penitenciaria